Model for Projects Observatories: A Preliminary Study - Vieira, Jeferson Kenedy Morais; de Farias, Ivaldir Honório; de Moura, Hermano Perrelli (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
In the organizations and projects, the observation has been defined by the transparency construct in the recent literature. The development of tools to systematize transparency has presented as a challenge to organizations. In this sense, the observatories are presented as information systems that support the collection, organization, storage, analysis, and observation publications, providing transparency. Nowadays, it is possible to identify the existence of observatories related to the most variable themes, such as health, environment, social media, cities, web, among others. In addition to that, projects and their management may also benefit from the development of these observatories. The use of observatories in the most different areas of knowledge added a striking feature, typological diversity. There is not only one model of observatories; however, the diversity does not prevent from establishing guidelines that can guide these observatories. Before this scenario, this research aims to propose a model that contributes to the comprehension and the development of projects observatories. We developed a set of initial exploratory studies to achieve this research’s objective where ten projects were executed ten pilot projects of project observatories. In addition, we developed a systematic mapping of the literature on observatories. The initial exploratory studies and the systematic mapping of the literature gave rise to the preliminary version of the model for project observatories.